Intermodal Consistency of Whole‐Brain Connectivity and Signal Propagation Delays - Jedynak, Maciej; Troisi Lopez, Emahnuel; Romano, Antonella; Jirsa, Viktor; David, Olivier; Sorrentino, Pierpaolo (Human brain mapping, 2025)
ABSTRACT Measuring propagation of perturbations across the human brain and their transmission delays is critical for network neuroscience, but it is a challenging problem that still requires advancement. Here, we compare results from a recently introduced, noninvasive technique of functional delays estimation from source‐reconstructed electro/magnetoencephalography, to the corresponding findings from a large dataset of cortico‐cortical evoked potentials estimated from intracerebral stimulations of patients suffering from pharmaco‐resistant epilepsies. The two methods yield significantly similar probabilistic connectivity maps and signal propagation delays, in both cases characterized with Pearson correlations greater than 0.5 (when grouping by stimulated parcel is applied for delays). This similarity suggests a correspondence between the mechanisms underpinning the propagation of spontaneously generated scale‐free perturbations (i.e., neuronal avalanches observed in resting state activity studied using magnetoencephalography) and the spreading of cortico‐cortical evoked potentials. This manuscript provides evidence for the accuracy of the estimate of functional delays obtained noninvasively from reconstructed sources. Conversely, our findings show that estimates obtained from externally induced perturbations in patients capture physiological activities in healthy subjects. In conclusion, this manuscript constitutes a mutual validation between two modalities, broadening their scope of applicability and interpretation. Importantly, the capability to measure delays noninvasively (as per MEG) paves the way for the inclusion of functional delays in personalized large‐scale brain models as well as in diagnostic and prognostic algorithms. The spatio‐temporal spreading of waves of activities across the brain can be quantified utilizing either intracranial electrodes or, noninvasively, magnetoencephalography. We present to what extent these two different techniques can converge, with respect to the quantification of both the spatial spreading and the corresponding delays.